2012
DOI: 10.1002/ptr.4786
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Inhibitory Activities of Four Indian Medicinal Plant Extracts and their Major Components on Rat Aldose Reductase and Generation of Advanced Glycation Endproducts

Abstract: The polyol enzyme aldose reductase (AR) and advanced glycation endproducts (AGEs) play an important role in diabetic complications such as cataracts. The purpose of this study was to investigate four standardized plant extracts used for the treatment of diabetes and related diseases, and their principal components for AR inhibitory activity and to find out their influence in diabetic complications. Thus, Boswellia serrata Triana & Planch. (Burseraceae), Lagerstroemia speciosa (L.) Pers. (Lythraceae), Ocimum gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 32 publications
1
23
0
2
Order By: Relevance
“…Interestingly, the MeOH extract of the aerial parts of W. subsessilis contains triterpenoids such as corosolic acid, which has been shown to exhibit strong ARI effects. Corosolic acid has a structure that is closely related to those of other known ARIs, such as ganoderic acid C2 and ganoderenic A [19,20,21]. These related studies support that W. subsessilis contains ARIs.…”
Section: Resultssupporting
confidence: 54%
“…Interestingly, the MeOH extract of the aerial parts of W. subsessilis contains triterpenoids such as corosolic acid, which has been shown to exhibit strong ARI effects. Corosolic acid has a structure that is closely related to those of other known ARIs, such as ganoderic acid C2 and ganoderenic A [19,20,21]. These related studies support that W. subsessilis contains ARIs.…”
Section: Resultssupporting
confidence: 54%
“…Suppression of pancreatic islet tissue atrophy and apoptosis of periinsular cells mediated by anti-caspase 3 are among its main antidiabetic mechanisms (Shehata et al, 2011(Shehata et al, , 2012. Rao et al (2013) reported that the oleo-gum resin and the isolated compound boswellic acid improve chronic diabetic complications via suppressing polyol enzyme aldose reductase and reduction of advanced glycation endproducts in vivo in rat lens and rat kidney as well as in vitro in human recombinant cell. In addition, B. carterii oleo-gum resin exhibited antidiabetic potential through an increase in serum insulin, regeneration of the β-cells of Langerhans islets as well as elevating glycogenesis and reducing glycogenolysis in rats with alloxan-induced type 1 diabetes (Helal et al, 2005).…”
Section: Boswellia Carterii and B Serrata (Burseraceae)mentioning
confidence: 99%
“…Thus, eremanthin possessed hypoglycemic and hypolipidemic activities and hence it could be used as a drug for treating diabetes (Eliza et al, 2009b). Boswellic acid isolated from the Boswellia serrataTriana & Planch(Rao et al, 2013) was found to be very effective at a dose of 10 mg/kg in-vivo and 10, 50 and 100 μg/ml for in-vitro assay. It acts by inhibiting the aldose reductase and formation of AGEs.…”
mentioning
confidence: 99%